2019
DOI: 10.2478/bsrj-2019-019
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on the Doing Business Index: a Machine Learning Approach

Abstract: Background: The World Bank (WB) acknowledged the importance of business regulatory environment and therefore created a metric which ranks 190 countries based on their level of business regulation for domestic firms measured by the Doing Business Index (DBI).Objectives: The question which attracted our attention is whether all the observed entities should be given the same weighting scheme.Methods/Approach: The approach we propose as an answer is two-fold. First, we cluster the countries covered by the DBI. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Moreover, countries with a high score on the DBI index tend to have a lower level of corruption and a higher level of business activity. The DBI index as an important indicator of the business regulatory environment was analysed by Maricic et al (2019) and Holden and Pekmezovic (2020). However, their findings revealed that the weighting scheme and conceptual grounds are not appropriate for all countries, which can result in discrepancies compared to other global multi-criteria indices.…”
Section: Dbi Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, countries with a high score on the DBI index tend to have a lower level of corruption and a higher level of business activity. The DBI index as an important indicator of the business regulatory environment was analysed by Maricic et al (2019) and Holden and Pekmezovic (2020). However, their findings revealed that the weighting scheme and conceptual grounds are not appropriate for all countries, which can result in discrepancies compared to other global multi-criteria indices.…”
Section: Dbi Indexmentioning
confidence: 99%
“…Slightly dissimilar outputs are presented by the DBI index (see Kiselakova et al, 2019b), where the quality of the business environment in the Baltic countries, Poland, and Germany have ranked alike, achieving the best results. The discrepancy between the subsets of countries formed by different indices may be caused by different factors used to form the applied measures (Perenyi et al, 2020) or, as stated by Maricic et al (2019), by the incorrect weighting scheme used in some global indices (DBI index).…”
Section: Overall Assessmentmentioning
confidence: 99%
“…These three variables include starting a business, dealing with firms' establishment's permits, and registering multinational business property. The concepts were drawn from but not limited to references [50][51][52][53].…”
Section: Concept Framing Model Specifications Validity Test and Analy...mentioning
confidence: 99%
“…Predictive analytics more specifically, has been used in many business applications such as customer relationship management, predicting crimefighting in law enforcement, predicting warranty problems for automobile manufacturers, predicting change in stock price, etc. (Chan, 2007;Maričić et al, 2019). In the past few years, different methods for validating the reliability prediction model of electric products were used such as time series models and the ARIMA model, fuzzy methods, neural networks and expert systems (Li et al, 2010).…”
Section: Related Workmentioning
confidence: 99%